Professor Ninian Smart speaking on Religion and nationalism: Bath, UK, 22 March 1994 - Smart, Ninian (UCC, University College Cork, 2020)
On Tuesday 22 March 1994, Professor Ninian Smart, by then Professor Emeritus of the Universities of Lancaster and Santa Barbara, spoke at Bath College of Higher Education (now Bath Spa University), UK, to an audience of undergraduates, postgraduates and academic staff on the topic of religion and nationalism. The event was hosted by the student 'World View Society" attached to the Study of Religions department. This is a rare video of Ninian Smart's lecturing style. Ninian Smart was one of the leading figures in the development of the modern academic study of religions in both UK and USA. Through Brian Bocking, who studied under Smart at Lancaster University in the 1970s, Smart's approach helped to shape the Study of Religions programme at UCC